2007
DOI: 10.1007/bf03325998
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Zn, Cu, Pb and Ni contamination in wetland soils and plants in the Lake Victoria basin

Abstract: ABSTRACT:The impact of waste disposal on trace metal contamination was investigated in eleven wetlands in the Lake Victoria Basin. Samples of soil, water and plants were analysed for total Zn, Cu, Pb and Ni concentrations using flame atomic absorption spectrophotometry. The trace metal concentrations in soil were the highest in Katanga wetland with the highest mean concentrations of 387.5±86.5 mg/kg Zn, 171.5±36.2 mg/kg Pb, 51.20±6.69 mg/kg Cu and 21.33±2.23 mg/kg Ni compared to the lowest levels observed at B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 9 publications
(7 reference statements)
6
36
2
Order By: Relevance
“…The high concentration of heavy metals was stated in the surface soil horizons (0-25 cm), which was mainly of anthropogenic origin. It was also confirmed by the studies of Dusza et al (2013) and Nabulo et al (2008). The elevated contents of heavy metals in the surface horizons of sandy soils are usually a result of an increased organic matter and the soil capacity for retaining heavy metals.…”
Section: Content Of the Selected Heavy Metals In Soilsupporting
confidence: 60%
See 1 more Smart Citation
“…The high concentration of heavy metals was stated in the surface soil horizons (0-25 cm), which was mainly of anthropogenic origin. It was also confirmed by the studies of Dusza et al (2013) and Nabulo et al (2008). The elevated contents of heavy metals in the surface horizons of sandy soils are usually a result of an increased organic matter and the soil capacity for retaining heavy metals.…”
Section: Content Of the Selected Heavy Metals In Soilsupporting
confidence: 60%
“…Nabulo et al (2008) found that the accumulation of heavy metals in surface soil level is closely correlated with the operation of the illegal deposit of waste. The high content of zinc, copper, lead and nickel was found directly beneath the waste in samples taken from the object C (Table 3).…”
Section: Content Of the Selected Heavy Metals In Soilmentioning
confidence: 99%
“…[2]. Processing of the this product requires heavy metals [7][8][9]. Giving the apparent influence of pH large volume of water which in addition to some other on these physiochemical properties, developing the solid substances forms part of the waste.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these findings differ from the experience in some other parts ofAfrica, where the application of large volumes of partially treated or untreated wastewater has adversely affected both surface water bodies and the urban and peri-urban farmers using these water bodies as sources of irrigation (Keraita and Drechsel, 2004). Also, in their studies in the Lake Victoria Basin, Nabulo et al (2008) found that heavy metals accumulated in wetlands used for wastewater disposal, the highest levels being recorded in wetlands receiving wastewater from multiple industrial sources.…”
Section: Introductionmentioning
confidence: 99%
“…Rusan et al (2007) concluded that continuous irrigation with wastewater could lead to accumulation of salts, plant nutrients and heavy metals (with the exception of Pb and Cd) in soils beyond crop tolerance levels. Also according to Nabulo et al (2008), uptake of trace metals from soil differs from plant to plant and from site to site. Thus, there is need for sustained studies in order to fully analyze and understand the long term environmental impacts of the use of treated sewage water for crop irrigation.…”
Section: Introductionmentioning
confidence: 99%